MEASURING THE LEVEL OF INFLUENCE OF SOME FACTORS ON THE QUALITY OF AUDITING FROM THE POINT OF VIEW OF AUDITORS (Neo Scientific Peer Reviewed Journal, 2023)
This study aims to know the factors affecting the quality of auditing from the point of view of auditors, and to come up with results and recommendations that contribute to raising and developing the performance of audit offices, while providing some guidance to government agencies and associations regulating the profession that help to find effective professional control over auditing, and to achieve the objectives of this study, some hypotheses have been formulated to achieve this and answer its questions. The researcher followed the descriptive analytical approach in the research and designed and distributed a scientific questionnaire to the study community, which is represented by the owners of audit offices.Using SPSS also, the researcher analyzed the questionnaire data through the statistical program various statistical tests, and the study reached a set of results, the most important of which is the existence of a significant positive impact on the quality of auditing and between both scientific qualification and scientific experience and the auditor's familiarity with generally accepted auditing standards, and the organization of the audit office, its size, reputation and fame. While the results showed that there were no statistically significant differences in the relationships affecting the quality of auditing from the point of view of the auditors according to the personal characteristics of the auditors. In light of the results of the study, the researcher recommended a set of recommendations, the most important of which are: attention to scientific and professional qualification and sufficient practical experience for workers in audit offices, with the need to focus on keeping pace with modern developments of the profession, and the research also recommended official authorities and professional associations to adopt local accounting and audit standards, and to review the legislation and laws regulating the profession in order to address its shortcomings and shortcomings, while giving professional associations the status of mandatory for the directives and instructions issued by them